The use of 'Check Pronunciation' & "Talking Tom' application in a Malaysian ESL classroom - Azmi, Mohd Zamri; M. Anthony, Elizabeth (Penerbit UTHM, 2020)
The need for learning and having a decent reading skill are indeed crucial in this modern-information age. It is extremely requires as a part of life obligations for any individual who intends to pursue for a basic good living such as getting the formal education and finding a stable job (Means, 2010). ..